Pijat Woolwich Saat Kehamilan TM3 terhadap Kecukupan ASI pada Ibu Menyusui dan Bayi Baru Lahir - Elly, Nur; Buston, Erni; Sari, Dewi Tarita; Mardiani, Mardiani; Darma, Dimas Dewa (Universitas Malahayati, 2024)
ABSTRACT Breast milk is a very important nutrient, especially for the life and survival of newborns. Breastfeeding in early life is often problematic. The purpose of the study was to determine the effect of Woolwich massage during TM 3 pregnancy on the adequacy of breast milk in breastfeeding mothers and newborns. This study uses an experimental method with a quasi-experimental design (quasi-experimental study), with a post-test only research design with a control group design. The population is all 3rd trimester pregnant women who carry out ANC at BPM Herma Nelis and Susi Irma, followed up until the child is born at the age of 1 week. Sampling using consecutive sampling technique. The number of respondents was 40 people consisting of 20 respondents for each intervention and control group. The intervention given was woolwich massage while the control group was given marmet massage. Data collection is done by Consecutive sampling. Data analysis through univariate and bivariate analysis with the Mann Whitney and Wilcoxon tests. The results showed that the p value was 0.016 (p value <0.05) meaning that there was a difference in the average score of breastfeeding adequacy between groups. This shows that there is an effect of Woolwich massage on the adequacy of breast milk in nursing mothers and newborns. Woolwich massage can be used as an effort to stimulate milk production. Keywords: Woolwich, Adequacy of Breast Milk, Breastfeeding Mother, Newborn ABSTRAK ASI merupakan nutrisi yang sangat penting terutama bagi kehidupan dan kelangsungan bayi baru lahir. Pengeluaran ASI di awal kehidupan seringkali mengalami masalah. Tujuan penelitian untuk mengetahui “pengaruh pijat Woolwich saat kehamilan TM 3 terhadap kecukupan ASI pada Ibu menyusui dan bayi baru lahir. Penelitian ini menggunakan metode eksperimen dengan desain eksperimen semu (quasi experiment study), dengan rancangan penelitian post test only with control group design. Populasi adalah seluruh ibu hamil trimester 3 yang melaksanakan ANC di BPM Herma Nelis dan Susi Irma yang diikuti sampai dengan anak lahir usia 1 minggu. Pengambilan sampel menggunakan teknik consecutive sampling. Jumlah responden 40 orang yang terdiri dari 20 responden untuk setiap kelompok intervensi dan kontrol. Intervensi yang diberikan adalah pijat woolwich sedangkan kelompok kontrol diberikan pijat marmet. Pengumpulan data dilakukan dengan cara Consecutive sampling. Analisis data melalui analisis univariat dan bivariat dengan uji mann whitney dan wilcoxon. Hasil penelitian menunjukkan bahwa nilai p value 0.016 (p value,05) artinya ada perbedaan nilai rata-rata skor kecukupan ASI antar kelompok. Hal ini menunjukan bahwa ada pengaruh pijat woolwich terhadap kecukupan ASI pada ibu menyusui dan bayi baru lahir. Pijat Woolwich dapat digunakan sebagai salah satu upaya untuk menstimulus produksi ASI. Kata Kunci: Woolwich, Kecukupan ASI, Ibu Menyusui, Bayi Baru Lahir